2022
DOI: 10.3389/fpls.2021.822907
|View full text |Cite
|
Sign up to set email alerts
|

Application of an Ovate Leaf Shape Model to Evaluate Leaf Bilateral Asymmetry and Calculate Lamina Centroid Location

Abstract: Leaf shape is an important leaf trait, with ovate leaves common in many floras. Recently, a new leaf shape model (referred to as the MLRF equation) derived from temperature-dependent bacterial growth was proposed and demonstrated to be valid in describing leaf boundaries of many species with ovate leaf shape. The MLRF model’s parameters can provide valuable information of leaf shape, including the ratio of lamina width to length and the lamina centroid location on the lamina length axis. However, the model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…Leaves are the most active and primary photosynthetic plant organ (Elser et al, 2010 ; Yang et al, 2019 ), their size and structure exhibit a tradeoff between the support cost and photosynthetic returns during plant adaptation to environmental changes (Shi et al, 2020 , 2022 ; Guo et al, 2021 ; Li et al, 2022a , b ), and leaf stoichiometry can reflect the tradeoff formed in this evolution from the angle of leaf chemical elements and its spatio-temporal variations (Baxter and Dilkes, 2012 ; Cao et al, 2020 ; Zhu et al, 2020 ). Leaf C/N and C/P were widely accepted as effective indicators of plants' N and P use efficiency and growth rate, and their lower values indicated lower nutrient utilization efficiency and higher plant growth (Weidner et al, 2015 ; Sun et al, 2017 ; Cao et al, 2020 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Leaves are the most active and primary photosynthetic plant organ (Elser et al, 2010 ; Yang et al, 2019 ), their size and structure exhibit a tradeoff between the support cost and photosynthetic returns during plant adaptation to environmental changes (Shi et al, 2020 , 2022 ; Guo et al, 2021 ; Li et al, 2022a , b ), and leaf stoichiometry can reflect the tradeoff formed in this evolution from the angle of leaf chemical elements and its spatio-temporal variations (Baxter and Dilkes, 2012 ; Cao et al, 2020 ; Zhu et al, 2020 ). Leaf C/N and C/P were widely accepted as effective indicators of plants' N and P use efficiency and growth rate, and their lower values indicated lower nutrient utilization efficiency and higher plant growth (Weidner et al, 2015 ; Sun et al, 2017 ; Cao et al, 2020 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These phenomena reflect the response of plants to environmental heterogeneity by phenotypic plasticity. Moreover, some studies reported that the interaction between plants and environmental factors could change the biomass allocation and the investmentbenefit-cost relationship of plants, which may be a trade-off between various traits of plant organs (Liu M. D. et al, 2020;Shi et al, 2020b;Li et al, 2021;Shi et al, 2022). The trade-off mean that an organism gains benefits from one trait, another trait pays appropriate costs.…”
Section: Introductionmentioning
confidence: 99%
“…In order to cope with this limitation, Shi et al (2021b) developed an ovate and obovate leaf shape model using leaf length and width and a third parameter representing the distance from the leaf base to the point on the leaf length axis associated with maximum leaf width. Consequently, Li et al (2021c) defined the “centroid ratio” (as the ratio of this third parameter to leaf length) to quantify the extent of the deviation of the leaf centroid from the midpoint of leaf length. Using this model, Li et al (2021c) found that the centroid ratio is significantly correlated with the ratio of leaf petiole mass to lamina mass for two Lauraceae species ( Cinnamomum camphora , and Machilus leptophylla ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, Li et al (2021c) defined the “centroid ratio” (as the ratio of this third parameter to leaf length) to quantify the extent of the deviation of the leaf centroid from the midpoint of leaf length. Using this model, Li et al (2021c) found that the centroid ratio is significantly correlated with the ratio of leaf petiole mass to lamina mass for two Lauraceae species ( Cinnamomum camphora , and Machilus leptophylla ). Therefore, the centroid ratio is a potentially a good quantitative index of leaf shape.…”
Section: Introductionmentioning
confidence: 99%